Bone mass in schizophrenia and normal populations across different decades of life - Renn, Jenn-Huei (BioMed Central, 2009)
BACKGROUND: Chronic schizophrenic patients have been reported as having higher osteoporosis prevalence. Survey the bone mass among schizophrenic patients and compare with that of the local community population and reported data of the same country to figure out the distribution of bone mass among schizophrenic patients. METHODS: 965 schizophrenic patients aged 20 years and over in Yuli Veterans Hospital and 405 members aged 20 and over of the community living in the same town as the institute received bone mass examination by a heel qualitative ultrasound (QUS) device. Bone mass distribution was stratified to analyzed and compared with community population. RESULTS: Schizophrenic patients have lower bone mass while they are young. But aging effect on bone mass cannot be seen. Accelerated bone mass loss during menopausal transition was not observed in the female schizophrenic patients as in the subjects of the community female population. CONCLUSION: Schizophrenic patients have lower bone mass than community population since they are young. Further study to investigate the pathophysiological process is necessary to delay or avoid the lower bone mass in schizophrenia patients.